코로나 바이러스 확산억제를 위한 환경 및 건축마감재료 고찰 - 항바이러스 재료 관련 해외 문헌을 중심으로 - 박용현; 이현진; 권순정 (의료·복지 건축, 2023)
Purpose: Currently, research on environmental conditions and finishing materials for medical facilities with proven antiviral performance is poor in Korea. Through this study, we have explored environmental characteristics and finishing materials that can be used to control cross-infection when constructing medical facilities. Methods: Experiments in overseas papers related to antiviral effects of environmental conditions, spatial compartments, and interior finishes have been analyzed. Results: The higher the temperature, the higher the humidity, and the higher the illuminance of sunlight, the lower the viability of the corona-virus. The proliferation of viruses was suppressed on the surface of the copper alloy. Materials such as brushed steel are the ones that maintain the strongest viability. Among the characteristics of the surface, survival and propagation power differ depending on whether it is porous or hydrophilic. In the case of infection ward actually operated in Italy, the presence of airborne viruses in contaminated and non-contaminated spaces differed significantly. Corona-virus has been identified in reachable parts such as door handles and medical shelves in quasi-contaminated spaces, which are spaces between contaminated and non-contaminated spaces, but the corona-virus has not been identified in cases of out-of-touch walls. Implications: It is necessary to evaluate the performance by testing the construction finishing materials of infection control facilities according to domestic conditions.
Keywords: COVID-19; SARS-CoV-2; Finishing materials; Environmental condition; Antiviruses; 코로나19; 코로나 바이러스; 건축마감재료; 환경조건; 항바이러스